Synergistic enhancement of tribological performance and thermal stability in R-1234yf refrigeration systems using graphene oxide -silver hybrid nanolubricants - Yamini S; Sekar S; Sivakami Sundari M; Senthil Kumar K (Case Studies in Thermal Engineering)
This study investigates the synergistic enhancement of tribological performance and thermal stability in R-1234yf refrigeration systems through the incorporation of graphene oxide -silver (GO-AgNPs) hybrid nano additives in polyol ester (POE) lubricants. GO-AgNPs hybrids were synthesized and dispersed in POE at concentrations of 0.1, 0.3, and 0.5 wt%. The nanolubricants were characterized using X-Ray Diffraction (XRD), scanning electron microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR) and TGA/DTA techniques. XRD analysis confirmed the presence of GO (2θ = 10.8°) and face-centered cubic AgNPs (AgNPs) with crystallite sizes of 18.5–20.1 nm. SEM imaging revealed well-dispersed graphene oxide (GO) sheets (2–5 μm) decorated with spherical silver nanoparticles (AgNPs) (20–25 nm), with some agglomeration observed at higher concentrations. FTIR spectroscopy indicated weak hydrogen bonding between GO functional groups and POE carbonyl groups without chemical modification of the base lubricant. Thermal analysis demonstrated significant stability enhancement, with decomposition onset temperature increasing from 298 °C (pure POE) to 318 °C (0.5 wt% GO-AgNPs). The hybrid nanolubricants exhibited superior tribological performance in R-1234yf systems, reducing friction coefficients by up to 42 % and wear rates by 53 % compared to pure POE. This was attributed to the formation of self-healing tribofilms facilitated by the thermally activated AgNPs and the laminar structure of GO. The 0.3 wt% GO-AgNPs concentration provided the optimal balance between enhanced performance and dispersion stability. These findings demonstrate the potential of GO-AgNPs hybrid nanolubricants for improving the efficiency and reliability of environmentally friendly R-1234yf refrigeration systems through synergistic enhancement of lubricant properties.